2019
DOI: 10.1038/s41598-019-44959-w
|View full text |Cite
|
Sign up to set email alerts
|

A comparative finite element analysis of maxillary expansion with and without midpalatal suture viscoelasticity using a representative skeletal geometry

Abstract: The goal of this investigation was to adapt and incorporate a nonlinear viscoelastic material model representative of the midpalatal suture’s viscoelastic nature into finite element analysis simulations of maxillary expansion treatment. Step-wise displacements were applied to a partial skull geometry to simulate treatment using an expansion screw appliance. Four simulation cases were considered for the midpalatal and intermaxillary sutures: 1. Neglecting suture tissue; 2. Linear elastic properties; 3. Viscoela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Palatal expansion has been widely used for the transverse discrepancy or maxillae hypoplasia, which is the main approach to stimulate bone regeneration around the suture area during orthodontics treatment 1‐3 . Palatal expansion is based on mechanical force‐induced bone remodeling, 4,5 but its underlying biological mechanisms remains largely unknown. It has been reported that osteoclasts played a crucial role during orthodontic tooth movement (OTM) and palatal expansion process 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Palatal expansion has been widely used for the transverse discrepancy or maxillae hypoplasia, which is the main approach to stimulate bone regeneration around the suture area during orthodontics treatment 1‐3 . Palatal expansion is based on mechanical force‐induced bone remodeling, 4,5 but its underlying biological mechanisms remains largely unknown. It has been reported that osteoclasts played a crucial role during orthodontic tooth movement (OTM) and palatal expansion process 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that as the number of activations increase, a small strain relaxation between activations occurs, which can be related to viscoelastic properties of the region in which the FBGs are positioned. The viscoelastic property of the midpalatal suture is important on the displacements analysis [30] and the sensor capability of estimating some viscoelastic parameters, such as the strain relaxation, result in important analysis of the palatal region, which can be assessed in the future. The temperature was kept constant during the tests and the differences between both appliances are not due to temperature variations.…”
Section: Resultsmentioning
confidence: 99%
“…Widening the maxilla expands the midpalatal suture (MPS) and the intermaxillary suture (IMS). When they are not fused, it is connective tissue and behaves viscoelastically in response to externally applied forces, 21 It has been shown that the activation of anchored miniscrews, for slow maxillary expansion (SME= one turn per day) vs fast maxillary expansion (RME= 2 turns per day), SME provides a better experience for the patient, however there is no statistical difference. EMR patients reported headaches and dizziness.…”
Section: Discussionmentioning
confidence: 99%